Aryl hydrocarbon receptor ligands increase ABC transporter activity and protein expression in killifish (Fundulus heteroclitus) renal proximal tubules - Mahringer, Anne; Bernd, Alexandra Marion; Miller, David S.; Fricker, Gert (Biological chemistry, 2019)
Many widespread and persistent organic pollutants, for example, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and some polychlorinated biphenyls, activate the aryl hydrocarbon receptor (AhR) causing it to translocate to the cell nucleus where it transactivates target genes, increasing expression of a number of xenobiotic metabolizing enzymes as well as some transporters. AhR’s ability to target transporters within the kidney is essentially unexplored. We show here that exposing isolated killifish (Fundulus heteroclitus) renal proximal tubules to micromolar β-naphthoflavone (BNF) or nanomolar TCDD roughly doubled the transport activity of Multidrug resistance-associated proteins Mrp2 and Mrp4, P-glycoprotein (P-gp) and Breast cancer resistance protein (Bcrp), all ATP-driven xenobiotic efflux pumps and critical determinants of renal xenobiotic excretion. These effects were abolished by actinomycin D and cycloheximide and by the AhR antagonist, α-naphthoflavone, indicating that increased transport activity was dependent on transcription and translation as well as ligand binding to AhR. Quantitative immunostaining of renal tubules exposed to BNF and TCDD showed increased luminal membrane expression of Mrp2, Mrp4, P-gp and Bcrp. Thus, in these renal tubules, the four ABC transporters are targets of AhR action.